Social Support dan Perceived Benefit Berpengaruh Terhadap Kepatuhan Pasien Prolanis di Wilayah Kerja Puskesmas Dlingo Bantul - Widarto; Prasetya, Joko; Anggraeni, Novita Ana (Jurnal Indonesia Sehat, 2025)
Background: Patient adherence to the Chronic Disease Management Program (Prolanis) remains a challenge, particularly in semi-rural areas. While social and cognitive factors are known to influence health behavior, limited studies have emphasized the role of social support and perceived benefit in the Prolanis context. Objective: To examine the influence of social support and perceived benefit on patient adherence to Prolanis at Dlingo Community Health Center, Bantul. Methods: A quantitative cross-sectional study involving 163 active Prolanis participants. Data were analyzed using chi-square tests and binary logistic regression. Results: Both social support (OR=5.026; p<0.05) and perceived benefit (OR=5.637; p<0.05) were significantly associated with adherence, confirming their role as key predictors, alongside other Health Belief Model variables. Conclusion: Social support and perceived benefit substantially contribute to improving Prolanis adherence. This highlights the importance of holistic community nursing interventions through contextual education and engagement of families and health cadres.